Satwagia Animal Clinic Business Transformation Strategy - Muhammad Balya Rafa Zahran; Raden Dikky Indrawan; Siti Jahroh (Eduvest - Journal of Universal Studies, 2025)
Satwagia’s veterinary clinic faces a performance paradox: despite strategic advantages like vertical integration and superapps amid a 9.5% CAGR animal care market, systemic operations remain suboptimal. This is evident in outlet closures and missed revenue targets. Meanwhile, the sector is driven by the humanization trend, causing a social paradigm shift and necessitating a transformation strategy for Satwagia. This case study formulates a strategy by diagnosing the gap between assets and execution. Using a three-stage formulation framework with expert input, quantitative analysis yielded an Internal Factor Evaluation (IFE) Matrix score of 2.238 (average) and an External Factor Evaluation (EFE) score of 3.023 (strong). Internal-External (IE) Matrix Mapping places Satwagia in Cell II (Grow and Build). The strong EFE score reflects defensive success; the weak IFE score reveals failure on the ‘O’ (organization) aspect within VRIO to fully exploit VRI assets. The recommended strategy is a two-phase transformation rather than expansion: (1) Build—urgent internal improvements in inventory and human resources to address core weaknesses; (2) Grow—technology-driven expansion to seize external opportunities sustainably. This research provides an empirical diagnosis of the knowing-doing gap in veterinary health care, offering critical guidance for Satwagia’s systemic transformation.